127 hours - Boyle, Danny; Franco, James; Tamblyn, Amber; Mara, Kate; Fox Searchlight Pictures (Los Angeles, California : Twentieth Century Fox Film Corporation, 2011)
Aaron Ralston has a passion for all things outdoors. But when a falling boulder traps him in a remote Utah canyon, a thrill-seeker's adventure becomes the challenge of a lifetime. Over the next five days, Ralston embarks on a remarkable personal journey in which he relies on the memories of family and friends-as well as his own courage and ingenuity-to turn adversity into triumph!.
Based on the book'Between a rock and a hard place' by Aaron Ralston.
Special features: Deleted scenes ; feature commentary with Danny Boyle, Christian Colson and Simon Beaufoy.
Directors of photography, Anthony Dod Mantle, Enrique Chediak ; production designer, Suttirat Larbab ; editor, Jon Harris ; original music, A.R. Rahman ; costume designer, Suttirat Larbarb.
James Franco, Amber Tamblyn, Kate Mara.
Shot on location in Utah.
DVD format, Anamorphic Widescreen (1.85:1), NTSC, Region 3, 5.1 Dolby Digital.
Keywords: Ralston, Aron, -- Drama; Rock climbing accidents -- Utah -- Canyonlands National Park; Mountaineering accidents -- Utah -- Canyonlands National Park; Action and adventure films; Bibliographical films